Odpowiedzi

2010-01-31T17:30:49+01:00
Sama mam wpisac swoje przykłady ?

przykład 1
2x - 10 = 12 / +10
2x - 10 +10 = 12 +10
2x = 22 /:2
2x :2 = 22: 2
x = 11
przykład 2
-x +2 = 8 /:2
-x + 2 - 2 = 8 - 2
-x = 6 /:(-1)
x = - 6
przykład 3
12x + 7 = 9x + 10 /-9x
12x + 7 - 9x = 9x + 10 - 9x
3x + 7 = 10 /-7
3x + 7 - 7 = 10 - 7
3x = 3 /:3
3x : 3 = 3 :3
x = 1
przykład 4
-1,5x + 2 = 9,5
-1,5x = 9,5 : 2
-1,5x = 7,5
x = 7,5 : (-1,5)
x = -5
przykład 5
3(1 - x) + 2 = -7
3 - 3x + 2 = -7
-3x + 5 = -7
-3x = -7 - 5
-3x = -12
x = 4
przykład 6
7-1,1x = 0,4 - 2,2x
7*10 - 1,1x *10 = 0,4 *10 - 2,2x *10
70 - 11x = 4 - 70
11x = -66
x = - 6
przykład 7
3(y + 6) - y = 2(y + 9)
3y + 18 - y = 2y + 18
2y + 18 = 2y + 18
2y - 2y = 18 - 18
0 = 0 - zdanie prawdziwe
przykład 8
4(x - 2) - 2(x - 4) = 5(x+1) - 3x
4x - 8 - 2x + 8 = 5x + 5 - 3x
2x = 2x + 5
2x - 2x = 5
0 = 5 - zdanie fałszywe
przykład 9
3(x+3) = 2(x+4)+x+1
3x + 9 = 2x + 8 + x + 1
3x + 9 = 3x + 9 - tożsamość
przykład 10
(2x - 1)² = 0
(2x - 1)(2x - 1) = 0
2x - 1 = 0
2x = 1
x = 1/2 ( tu ma był ułamek 1/2)
2 5 2